2003
DOI: 10.1001/archpsyc.60.10.974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of New Antipsychotic Medications

Abstract: Antagonism of D2-like dopamine receptors is the putative mechanism underlying the antipsychotic efficacy of psychotropic drugs. Positron emission tomographic studies suggest that the antipsychotic effect of dopamine receptor antagonists occurs within a therapeutic window between 60% and 80% (striatal) D2 receptor occupancy. The incidence of extrapyramidal side effects increases above the 80% threshold. However, the novel atypical antipsychotic drug, aripiprazole, occupies up to 95% of striatal D2-like dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(107 citation statements)
references
References 46 publications
3
96
0
8
Order By: Relevance
“…The first generation of neuroleptic drugs were shown to block D 2 receptors and have made a substantial contribution to the management of schizophrenia. 30 However, such compounds have a number of serious limitations. Firstly, they are not always effective.…”
Section: Cns Drug Discoverymentioning
confidence: 99%
“…The first generation of neuroleptic drugs were shown to block D 2 receptors and have made a substantial contribution to the management of schizophrenia. 30 However, such compounds have a number of serious limitations. Firstly, they are not always effective.…”
Section: Cns Drug Discoverymentioning
confidence: 99%
“…The suggestion of a 'therapeutic window' between 60 and 80% striatal D 2 receptor occupancy for sufficient treatment response and a 'ceiling' of around 80% occupancy for extrapyramidal side effects (EPS) was later confirmed by a number of other groups (Kapur et al, 2000a). This rule seems to apply also for most of the 'atypical' antipsychotics (Kapur et al, 1999), but not for partial agonists (Gründer et al, 2003a). Interestingly, the early PET studies with clozapine demonstrated that clozapine occupies striatal D 2 receptors to a significantly lesser extent than other antipsychotics, with the exception of quetiapine (Nordström et al, 1995;Kapur et al, 2000bKapur et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that the positive symptoms of schizophrenia are alleviated when 60% to 80% of dopamine D2-like neuroreceptors in the brain are occupied by antipsychotic drugs demonstrated by PET [6,15,22,23] represents a major advance in the development of novel drugs to treat people with schizophrenia. PET allows clinicians to determine the likely optimal dose of dopamine D2 receptor blocking drugs to produce a therapeutic effect with minimal adverse effects [17] .…”
Section: The Dopamine Hypothesis Of Schizophreniamentioning
confidence: 99%
“…PET allows clinicians to determine the likely optimal dose of dopamine D2 receptor blocking drugs to produce a therapeutic effect with minimal adverse effects [17] . Doses of typical antipsychotics resulting in greater than 80% occupancy of dopamine D2 receptors in the brain demonstrated by PET may increase the risk of the development of tardive dyskinesias, other movement disorders, and other adverse events likely with higher dosages [6,13,17,22,23] . Thus, imaging studies of the density and the distribution of dopamine D2 receptors before and after the administration of putative therapeutic agents for schizophrenia constitute a tool to identify likely therapeutic doses of novel agents.…”
Section: The Dopamine Hypothesis Of Schizophreniamentioning
confidence: 99%